Design and Experimental Investigation of a Self-Tuning Piezoelectric Energy Harvesting System for Intelligent Vehicle Wheels - Rui, Xiaobo; Zeng, Zhoumo; Zhang, Yu; Li, Yibo; Feng, Hao; Huang, Xinjing; Sha, Zhou (IEEE transactions on vehicular technology, 2020)
This article proposes a piezoelectric energy harvester to supply power for low-consumption devices in intelligent vehicle wheels. The harvester is embedded in the spoke and possesses the ability of self-tuning due to the centrifugal force in the rotational motion. A dynamic model suitable for design is derived through the Euler-Lagrange method and verified by experiments. In order to facilitate the design of the harvester, the concept of design factor is proposed and discussed. The wheel's rotational characteristics is measured by a road test and a harvester is designed for the R16 wheel. An experimental platform with Macro Fiber Composite is built and the output power of 0.61-6.28 mW is achieved at the wheel speeds from 40 to 120 kph on real road test. The results demonstrate that the proposed piezoelectric energy harvester can be applied to establish a wireless self-sufficient intelligent vehicle wheel system.